Utilization of chicken manure enriched with Lemna liquid organic fertilizer Lemna minor on cell density of Chlorella sp. - Rosyadi, Rosyadi; Agusnimar, Agusnimar; Khairul Hadi (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
One of the organic fertilizers that has the potential to be used to culture Chlorella sp. is chicken manure. However, to increase the content of nutrients in chicken manure, it must be enriched with liquid organic fertilizer (POC) in different doses. The purpose of this study was to determine the optimal dose of chicken manure enrichment using Lemna POC on the cell density of Chlorella sp. This study used a complete randomized design (CRD) with five treatments of three replicates, namely P0 giving 3 g/L chicken manure (control), P1 = 3 g/L chicken manure enriched with 4% Lemna POC, P2 = 3 g/L chicken manure enriched with 5% Lemna POC, P3 = 3 g/L chicken manure enriched with 6% Lemna POC, and P4 = 3 g/L chicken manure enriched with 7% Lemna POC. The results obtained the highest cell density of Chlorella sp. in the P3 treatment of 516.67 ± 6.29 ×104 cells/mL, a specific growth rate of 0.142 cells/mL/day, and a biomass weight of 0.39 g/L. From the results of the study, it can be concluded that the optimal dose of chicken manure enrichment to increase the cell density of Chlorella sp. is 6% Lemna POC in P3 treatment. Keyword: cell density, chicken manure, Chlorella sp., Lemna POC ABSTRAK Salah satu pupuk organik yang memiliki potensi dimanfaatkan untuk kultur Chlorella sp. adalah kotoran ayam. Namun untuk meningkatkan kandungan unsur hara pada kotoran ayam maka harus diperkaya dengan pupuk organik cair (POC) Lemna dengan dosis berbeda. Tujuan dari penelitian ini untuk mengetahui dosis pengayaan kotoran ayam yang optimal menggunakan POC Lemna terhadap kepadatan sel Chlorella sp. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan lima perlakuan tiga ulangan, yaitu P0 pemberian 3 g/L kotoran ayam (kontrol), P1 = 3 g/L kotoran ayam diperkaya 4% POC Lemna, P2 = 3 g/L kotoran ayam diperkaya 5% POC Lemna, P3 = 3 g/L kotoran ayam diperkaya 6% POC Lemna, dan P4 = 3 g/L kotoran ayam diperkaya 7% POC Lemna. Hasil penelitian diperoleh kepadatan sel Chlorella sp. tertinggi pada perlakuan P3 sebanyak 516,67 ± 6,29 ×104 sel/mL, laju pertumbuhan spesifik sebesar 0,142 sel/mL/hari dan berat biomassa sebesar 0,39 g/L. Dari hasil penelitian dapat disimpulkan bahwa dosis pengayaan kotoran ayam yang optimal untuk meningkatkan kepadatan sel Chlorella sp. adalah 6% POC Lemna pada perlakuan P3. Kata kunci: Chlorella sp., kepadatan sel, kotoran ayam, POC Lemna